Evaluation of orbital morphometry using 3D computed tomographic images in biological sex determination: A retrospective study - Sudhaa Mani Mani; S Yasmeen Ahamed; P Ambiga; Valarmathi Ramalingam; G Sivaraman; N Balan (Wolters Kluwer Medknow Publications, 2020)
Background: Forensic science, also known as Criminalistics is a field of science that uses science for investigation and its application in civil and criminal proceedings. One of the main challenges is to identify the dead during criminal and mass disaster investigations. Aim: The study aims to evaluate the morphometry of the orbital aperture and to verify its relationship with biological sex discrimination using three-dimensional Computed Tomography (3D CT). Study Design: This retrospective study involves 100 3D CT images of 50 males and 50 females (age 18-60 years). Materials and Methods: The exclusion criteria were congenital anomalies affecting the head and neck region, orbital fracture, systemic diseases affecting bone and head and neck tumor. Eight orbital parameters such as Orbital width, orbital height, orbital roof length, orbital floor-length, lateral orbital wall length, medial orbital wall length, intraorbital distance, and extra orbital distance were measured for all the 3D CT images using RadiAnt DICOM Viewer (64 bit). Statistical Analysis: Descriptive statistics including mean, standard deviation, and percentage distribution were calculated. Mann Whitney U-test assessed the comparison between groups. The linear regression equation and Wilk's lambda were also calculated for every parameter. Results: All the orbital measurements except for intraorbital distance were statistically significant between male and female subjects. Totally, 92.0% of the individuals were correctly classified. Conclusions: Orbital measurements were significantly larger in males than in females. Orbits exhibit the least dimensional change throughout one's life. Hence, it could be used as an adjunct in biological sex determination.